2004
DOI: 10.1016/j.jnucmat.2004.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and microscopic investigation of the corrosion of 316/316L stainless steel by lead–bismuth eutectic (LBE) at elevated temperatures: importance of surface preparation

Abstract: The corrosion of steel by lead-bismuth eutectic (LBE) is an important issue in proposed nuclear transmutation schemes. Steel samples were exposed to oxygen-controlled LBE at high temperature and exposure times that simulate actual reactor systems. Scanning electron microscopy (SEM), combined with energy-dispersive X-ray analysis (EDAX) and X-ray photoelectron spectroscopy (XPS), has been used to study post-exposure steel samples and unexposed controls. Our investigation of the reacted samples revealed preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…The AISI 316L austenitic stainless steel is widely used in industrial applications due to its good creep properties and oxidation resistance provided by the high alloy chromium content [1][2][3][4][5][6][7][8]. Several studies proposed that, at high temperature, chromia-forming alloys such as AISI 316L SS exhibit an oxide growth leading mainly to Cr 2 O 3 and Mn 1.5 Cr 1.5 O 4 formation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AISI 316L austenitic stainless steel is widely used in industrial applications due to its good creep properties and oxidation resistance provided by the high alloy chromium content [1][2][3][4][5][6][7][8]. Several studies proposed that, at high temperature, chromia-forming alloys such as AISI 316L SS exhibit an oxide growth leading mainly to Cr 2 O 3 and Mn 1.5 Cr 1.5 O 4 formation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Galerie et al have explained that the breakaway on a Fe-15%Cr alloy was induced by rapid growth of hematite at the metal/chromia interface, at 800-1000 °C, in Ar-15 vol.% H 2 O [23]. But in many cases, the chromia scale failure was related to the formation of the CrO 2 (OH) 2 and Cr(OH) 3 volatile hydroxides [28][29][30]. Evaporation can lead to the alloy chromium depletion resulting in the formation of an iron-rich non-protective scale.…”
Section: Introductionmentioning
confidence: 99%
“…The AISI 316L stainless steel is a technologically important material widely used in various sectors of industry due to its good corrosion resistance at high temperatures [1][2][3][4][5][6]. It has been shown that 100 h oxidation, in air, at 700°C leads to the presence of Cr 2 O 3 and Fe 2 O 3 protuberant areas in the oxide scale [7].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application, such materials are subjected to corrosive atmospheres and thermal cycling. Several studies [1][2][3][4][5][6] highlighted that, at high temperature, chromia-forming alloys such as AISI 316L stainless steels present an oxide growth leading mainly to chromia Cr 2 O 3 and spinel type oxide formation. However, in situ X-ray diffraction (XRD) studies have never been performed on AISI 316L specimens at 800°C in order to check if a change in the structural composition of the layer appears with time and if oxide phase transitions occur during cooling to room temperature as it was demonstrated on a AISI 304 substrate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since the minimum temperature in the system is limited by the melting point of LBE, it is necessary to increase the hot-leg temperature as much as possible. However, a major drawback in using liquid LBE at high temperatures elevation is the increasing solubility of many chemical elements [3,11,[13][14][15][16] and the potential for liquid-metal-assisted corrosion (LME) of the structural materials in contact with LBE [5,[11][12][13][14]. Besides the above mentioned phenomena, applying stress to the unprotected solid metals exposed to liquid metals, the former may experience liquid metal embrittlement (LME), characterized by premature brittle failure, depending on various parameters [72,73].…”
Section: Introductionmentioning
confidence: 99%